2013
DOI: 10.1021/jf402743e
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of α-Chitin Substrates with Varying Particle Size and Crystallinity Reveals Substrate Preferences of the Chitinases and Lytic Polysaccharide Monooxygenase of Serratia marcescens

Abstract: 1Industrial depolymerization of chitinous biomass generally requires numerous steps and the 2 use of deleterious substances. Enzymatic methods provide an alternative, but fundamental 3 knowledge that could direct potential development of industrial enzyme cocktails is scarce. 4We have studied the contribution of mono-component chitinases (ChiA, -B, and -C) and the 5 lytic polysaccharide monooxygenase (LPMO) from Serratia marcescens on depolymerization 6 of -chitin substrates with varying particle size and cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 31 publications
6
42
1
Order By: Relevance
“…B–F). The relative rate of Lm LPMO10 was similar to that of the well‐characterized LPMO, CBP21 from S. marcescens (Fig. B–F).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…B–F). The relative rate of Lm LPMO10 was similar to that of the well‐characterized LPMO, CBP21 from S. marcescens (Fig. B–F).…”
Section: Resultssupporting
confidence: 67%
“…These product profiles are essentially identical to those observed for CBP21 on the same substrates , and also show a lack of high degree of polymerization (DP) products for α‐chitin compared to β‐chitin. This has been suggested to be caused by the tighter packing of chitin chains in the α‐allomorph of these substrates, which prevents release of long oligosaccharides as a result of adhesion to the insoluble substrate .…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…As an alternative source of β-chitin we used squid pen chitin purchased from Yaegaki (Hayashida, Japan) exposed to cutter milling for 60 sec for particle size reduction (See ref. 41 for methods). Soluble chitosans with a degree of N -acetylation of 61% and 64% (F A 0.61 and 0.64), with a random distribution of N -acetylated and de- N -acetylated units 31 , were a gift from Professor Kjell M. Vårum from the Department of Biotechnology, Norwegian University of Science and Technology.…”
Section: Methodsmentioning
confidence: 99%
“…Under our conditions, there may be enough points for attack by the endo-acting ChiC, and the help from CBP21 is unnecessary initially. Interestingly, Nakagawa and co-workers observed that CBP21 hardly influenced the activity of ChiA on α-chitin 18. This finding was rationalized by possible different face preferences on the chitinous substrate for the two different enzymes.Previously, it has been shown that none of the chitinases of S. marcescens are capable of completely degrading the substrates used in our study by themselves 12,19.…”
mentioning
confidence: 99%